3D Reconstruction of Tree-Crown Based on the UAV Aerial Images - Chao Xu (Mathematical Problems in Engineering, 2015)
The algorithm for 3D reconstruction of tree-crown is presented with the UAV aerial images from a mountainous area in China. Considering the fact that the aerial images consist of little tree-crown texture and contour information, a feature area extraction method is proposed based on watershed segmentation, and the local area correlation coefficient is calculated to match the feature areas, in order to fully extract the characteristics that can reflect the structure of tree-crown. Then, the depth of feature points is calculated using the stereo vision theory. Finally, the L-system theory is applied to construct the 3D model of tree. The experiments are conducted with the tree-crown images from UAV aerial images manually. The experiment result showed that the method proposed in this paper can fully extract and match the feature points of tree-crown that can reconstruct the 3D model of the tree-crown correctly.